Gambaran Faktor-Faktor Yang Mempengaruhi Kecemasan Pada Ibu Hamil Trimester III dalam Menghadapi Persalinan di Klinik Mitra Delima - Nurlatifah, Neneng Siti Maryani; Fatimah, Siti; Heryani, Sri; Ningrum, Widya Maya (Journal of Midwifery and Public Health, 2024)
Anxiety in pregnant women often increases in the third trimester and can have a negative impact on the mother and fetus. According to the WHO in 2019, around 30% of pregnant women in the third trimester experienced anxiety when approaching delivery. This study aims to identify factors that affect anxiety in pregnant women in the third trimester at Mitra Delima Clinic in 2024. This research method is descriptive with the Accidental Sampling approach, involving 30 pregnant women in the third trimester who experience anxiety, using a questionnaire as a data collection tool. The results showed that the majority of respondents were between 20-35 years old (83.3%), while respondents who were considered at risk (<20 or >35 years) were 16.7%. Most of the respondents have a high school education (46.7%), followed by junior high school (40%), and elementary school (13.3%). All respondents work as housewives. Respondents with multigravida parity were more (53.3%) compared to primigravida (46.7%). All respondents had an income below Rp. 2,089,464. The majority of respondents have a lack of knowledge (53.3%). It is recommended that pregnant women increase antenatal care visits to prepare themselves physically and mentally for childbirth